Phyto - coenotic location and state of Allium regelianum A.Becker ex Iljin & Ferula orientalis L. populations to region “Ascania Nova” Biosphere Reserve (CHORNOMORSKI BOTANICAL JOURNAL, 2005)
The disturbution and ecologo-coenotic pecularities two rare species Allium regelianum and Ferula orientalis (included in Addition I Bern`s convention) to region “Ascania Nova” Biosphere Reserve are shown. The syntaxonomic scheme of the vegetation whith participant this species are present. The study vegetations rating to Festuco-Limonietea Karpov et Mirkin 1986, in composition Carici praecoxi-Elytrigietalia pseudocaesiae ord. nova.
Keywords: Allium regelianum, Ferula orientalis, ecology, coenology, “Ascania Nova” Biosphere Reserve.